(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
The article reflects on the importance of the media, primarily television, in the development of creative thinking in children. The features of the psychological impact of shows for children given on television on their cognitive abilities, creative thinking and increasing the wealth of speech are analyzed.